Role of Triphasic CT Scan in the Detection of Liver Masses: A Comprehensive Evaluation - Raad Abdalrahman Hameed, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The detection of liver hundreds is essential for the diagnosis and management of liver illnesses, along with benign lesions like hemangiomas and malignant tumors along with hepatocellular carcinoma (HCC). Triphasic CT scanning, which entails three stages of evaluation enhancement (arterial, portal venous, and not on time), provides detailed imaging of liver lesions and has emerge as a fashionable technique in liver mass detection because of its ability to differentiate among extraordinary sorts of lesions based totally on their vascular styles. Objective: This observe aims to assess the diagnostic performance of triphasic CT scans in detecting liver masses in 500 sufferers (250 males and 250 women, aged 25 years and above). The primary intention is to decide the sensitivity, specificity, and diagnostic accuracy of triphasic CT in figuring out benign as opposed to malignant lesions, as well as to investigate the correlation among imaging findings and final diagnosis. Methodology: This retrospective study included 500 patients who underwent triphasic CT imaging at Tikrit Teaching Hospital among 1st Jan. 2021 to 1st Feb. 2024. The sufferers have been divided into two companies: Group 1 (men, n=250) and Group 2 (girls, n=250), with a long time ranging from 25 to 80 years. This take a look at utilized a cross-sectional layout to assess the effectiveness of triphasic computed tomography (CT) in detecting and differentiating liver tumors amongst a pattern of 500 patients elderly 25 and older. Participants have been divided into groups based totally on intercourse (men and women) and similarly classified into age brackets (e.G., 25-34, 35-44, and so forth.) to make certain a balanced distribution. Each patient underwent a triphasic CT test, carried out in three awesome stages—arterial, portal venous, and behind schedule—to seize the vascular traits of the liver lesions. Results: In this have a look at of 500 instances, liver tumor distribution various appreciably through tumor type, age, and gender. Malignant tumors had been more prevalent than benign ones, accounting for 66% in adult males and 70% in ladies. For benign tumors, maximum cases have been in women over 50 years (54.7%) and guys elderly 30-50 years (29.4%). Malignant tumors were in particular commonplace in men aged 30-50 years (61.8%) and in ladies over 50 (56%). Age-sensible, the highest tumor prevalence passed off amongst people elderly 30-50 (49%) and people over 50 (43.5%), showing a fashion of increasing incidence with age for both benign and malignant tumors. Discussion: The findings show that triphasic CT is particularly touchy and specific for detecting liver loads, with first-rate diagnostic accuracy. The arterial phase was especially effective in identifying hypervascular lesions like HCC, at the same time as the behind schedule segment became critical in differentiating between benign and malignant lesions primarily based on washout patterns. The observe additionally showed that the average lesion length and age distribution should assist clinicians expect the chance of malignancy, with older sufferers much more likely to have malignant lesions. The barely higher sensitivity within the male organization suggests capability gender-based totally differences in lesion detection, which warrants further investigation. These results emphasize the cost of triphasic CT as an critical imaging device for liver mass detection and characterization, supplying essential statistics for clinical selection-making.